MENINGKATKAN HASIL BELAJAR SEPAK TAKRAW MELALUI PENDEKATAN PERMAINAN JALA HIP HOP (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
This study aimed to determine the improvement of learning outcomes through a sepak takraw game nets hiphop approach to fifth grade elementary school students Keputran Pekalongan city 01 school year 2012/2013.This study uses classroom action research was conducted in two cycles of the Cycle I and Cycle II. From theresults of research conducted, found that student achievement had peningkatakan from the initial conditions tothe first cycle to the second cycle, both from an increase in the average value of the high jump and the value oflearning mastery learning outcomes. The average value of learning outcomes in the conditions of the first cycleof 75.14%, 87.29% and Cycle II, so the average increase student learning outcomes from the first cycle to thesecond cycle was 12.15%. The average value of mastery learning outcomes of students as much as the initialcondition (14.29%), first cycle 8 students (57.14%), and the second cycle as many as 14 students (100%). Toincrease learning ability in sepak takraw motion can be seen from the KKM (75,00) who have mastery in thefirst cycle of students who pass the value of learning as much as 2 out of 14 students (14.29%) and the secondcycle is completed by 13 of 14 students overall or completed by 92.86%. Sepak takraw ability students inlearning this penjas have increased quite high.